Empowering Educational Leaders: Nurturing Strong Teaching and Learning Environments in Kenyan Schools. - Mrutu, Nipael; Ali, Zaituni; Mwang'ombe, Alice (Journal of Education and Practice, 2024)
Purpose: Kenya’s paradigm shifts in curriculum from content based to competence-based curriculum is geared towards improving the quality of education to meet the global demands. This prompts the need to build a firm foundation from early childhood education through appropriate classroom learning experiences and good leadership. This study explored educational leaders' practices in their management of primary schools in Kenya. Methodology: This article draws evidence from the Longitudinal Study which was designed among other things to establish the best practices that teacher educators can adopt to inform the professional learning of Student Teachers to become effective champion teachers, and leaders. The study adopted a mixed method approach with a sample size of 29, comprising 4 education officers, 25 head teachers in Mombasa and Kilifi counties in Kenya. Findings: The findings revealed that most education leaders have embraced transformative leadership styles and policies to motivate their subordinates through action research, portfolio, mentorship, coaching, collaboration, and networking. Findings revealed further that mentorship is key in educational leadership and thus should be regarded as a vital aspect in teacher education and in professional learning. Data also indicated that leadership styles differ in relation to the context. Unique Contribution to Theory, Policy and Practice: The leader’s role is deeply involved with setting the school’s direction; thus, teacher leadership preparation is essential for successful implementation of education processes and programs. Hence, we recommend that school leaders should be adequately prepared to face the tasks and the accompanying contextual challenges they face once assigned the responsibilities to lead institutions.